Role of Modern Corporate Culture in Companies Development - A. I. Sosnilo; D. A. Snetkova (Управленческое консультирование)
The article considers modern trends in the role of corporate culture in international companies and reveals the importance of corporate culture in the development of companies. It gives examples of successful construction of corporate culture, using human capital, supporting employees’s projects within companies. Also the article considers the vision of building a developed corporate culture by the leaders of large world and domestic companies.